An investigation of the market's pricing of auditor competence: Evidence from PwC's Oscars blunder. (April 2022) - Abbott, Lawrence J.; Buslepp, William L.
Abstract: On Sunday, February 26, 2017, PricewaterhouseCoopers (PwC) erred on live television when Brian Cullinan, PwC's U.S. Board Chairman and Managing Partner of PwC's Southwest region, handed the announcers the wrong envelope for Best Picture at the 2017 Academy of Motion Picture Arts and Sciences Awards Ceremony (hereafter, the Oscars). Cullinan's blunder represented a clear lack of competence in a non-audit service (NAS) context. Building on prior brand extension research, we hypothesize that market participants transfer their assessment of Cullinan's Oscars ceremony (i.e., NAS) incompetence to the financial statement audit competence of PwC's publicly traded audit clients. Consistent with this prediction, we find that abnormal returns in the days following the error are significantly lower for PwC clients in the region Cullinan managed, suggesting an impaired reputation for audit quality. However, losses experienced by PwC clients were restored within a month after the blunder, suggesting the durability of PwC's reputation in overcoming the initial impairment. Taken together, our evidence suggests that investors find the disclosure of audit partner identity to be informative.